Implementation of a Compact Spot-Scanning Proton Therapy System in a GPU Monte Carlo Code to Support Clinical Routine - Gajewski, Jan; Schiavi, Angelo; Krah, Nils; Vilches-Freixas, Gloria; Rucinski, Antoni; Patera, Vincenzo; Rinaldi, Ilaria (Frontiers in Physics, 2020)
The purpose of this work was to implement an fast Monte Carlo (MC) dose calculation tool, FRED, in The Maastro Proton Therapy centre in Maastricht (the Netherlands) to complement the clinical Treatment Planning System (TPS). FRED achieves high accuracy and computation speed by using physics models optimized for radiotherapy and extensive use of GPU technology for parallelization. We implemented the beam model of the Mevion S250i proton beam and validated it against data measured during commissioning and calculated with the clinical TPS. The beam exits the accelerator with a pristine energy of around 230 MeV and then travels through the dynamically extendable nozzle of the device. The nozzle contains the the range modulation system (RMS) and the multi-leaf collimator system named adaptive aperture. The latter trims the spots laterally over the 20x20 cm2 area at the isocenter plane. We use a single model to parametrise the longitudinal (energy, energy spread) and transverse (beam shape) phase space of the non-degraded beam in the default nozzle position. The range modulation plates and the adaptive aperture are simulated explicitly and moved in and out of the simulation geometry dynamically by FRED. Patient dose distributions recalculated with FRED were comparable with TPS and met clinical criteria. Calculation time was on the order of 10-15min for typical patient cases and future optimisation of the simulation statistics are likely to improve this further. Already now, Fred is fast enough to be used as tool for plan verification based on machine log files and daily (on-the-fly) dose recalculations in our facility.